Yeast Double Transporter Gene Deletion Library for Identification of Xenobiotic Carriers in Low or High Throughput - Almeida, Ludimila Dias; Silva, Ali Salim Faraj; Mota, Daniel Calixto; Vasconcelos, Adrielle Ayumi; Camargo, Antonio Pedro; Pires, Gabriel Silva; Furlan, Monique; Freire, Helena Martins Ribeiro da Cunha; Klippel, Angelica Hollunder [UNESP]; Silva, Suelen Fernandes [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Carazzolle, Marcelo Falsarella; et al. (Amer Soc Microbiology, 2021)
The routes of uptake and efflux should be considered when developing new drugs so that they can effectively address their intracellular targets. As a general rule, drugs appear to enter cells via protein carriers that normally carry nutrients or metabolites. A previously developed pipeline that searched for drug transporters using Saccharomyces cerevisiae mutants carrying single-gene deletions identified import routes for most compounds tested. However, due to the redundancy of transporter functions, we propose that this methodology can be improved by utilizing double mutant strains in both low- and high-throughput screens. We constructed a library of over 14,000 strains harboring double deletions of genes encoding 122 nonessential plasma membrane transporters and performed low-and high-throughput screens identifying possible drug import routes for 23 compounds. In addition, the high-throughput assay enabled the identification of putative efflux routes for 21 compounds. Focusing on azole antifungals, we were able to identify the involvement of the myo-inositol transporter, Itr1p, in the uptake of these molecules and to confirm the role of Pdr5p in their export. IMPORTANCE Our library of double transporter deletion strains is a powerful tool for rapid identification of potential drug import and export routes, which can aid in determining the chemical groups necessary for transport via specific carriers. This information may be translated into a better design of drugs for optimal absorption by target tissues and the development of drugs whose utility is less likely to be compromised by the selection of resistant mutants.
Keywords: nonessential transporter double-deletion library; plasma membrane transporter; drug uptake; drug efflux; xenobiotics; Saccharomyces cerevisiae; drug transport; genetic interactions; yeast